1987
DOI: 10.1111/j.1744-313x.1987.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of C4a Is a Genetic Determinant of Systemic Lupus Erythematosus in Three Ethnic Groups

Abstract: SUMMARY Systemic lupus erythematosus (SLE) has shown associations with the major histocompatibility complex (MHC) class II DR antigens and class III complement components C2 and C4 in previous studies. The primary susceptibility locus has been difficult to identify, however, on account of linkage disequilibrium within the MHC. We have studied C4A and C4B distributions in 63 Caucasoid, 75 Chinese and 51 Japanese SLE patients. All three populations showed a statistically significant increase in C4A*Q0 (null) all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(31 citation statements)
references
References 14 publications
1
28
2
Order By: Relevance
“…[28][29][30][31][32][33][34] C4A*Q0 is also associated with SLE susceptibility in multiethnic Asian populations, including Japanese and Chinese. 35 This result has been replicated in Korean, 19 Japanese 36 and Chinese, 37 but also not in Chinese 16 and Malaysian. 38 However, C4A*Q0 is known to be in linkage disequilibrium with HLA-DR3.…”
Section: Resultsmentioning
confidence: 93%
“…[28][29][30][31][32][33][34] C4A*Q0 is also associated with SLE susceptibility in multiethnic Asian populations, including Japanese and Chinese. 35 This result has been replicated in Korean, 19 Japanese 36 and Chinese, 37 but also not in Chinese 16 and Malaysian. 38 However, C4A*Q0 is known to be in linkage disequilibrium with HLA-DR3.…”
Section: Resultsmentioning
confidence: 93%
“…However, it should be noted that 2 erythrocyte blood group antigens, Rodgers and Chido, have been shown to correspond to the C4d region of C4A and C4B, respectively (16,28), suggesting that both C4A and C4B can bind to and persist on the surface membranes of normal erythrocytes. C4-null alleles or partial deficiency of C4A and/or C4B has been associated with human SLE (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of disease-related polymorphic genes, such as MHC class II, C4A, IgG heavy chain variable region, may also vary among groups (26,(38)(39)(40)(41)(42)(43)(44). Among Hispanics in Venezuela, a study of 41 patients also suggested an increased frequency of a phenotype containing at least one Fc␥RIIA-R131 gene (45).…”
Section: Discussionmentioning
confidence: 99%